Characterization of activated carbon, wood sawdust and their application for boron adsorption from water. (2nd January 2021) - Jaouadi, Mouna
ABSTRACT: Pinewood sawdust is a good precursor for activated carbon production. Activated carbon was prepared from sawdust by chemical activation using H3 PO4 at 300°C. The properties of sawdust and activated carbon were characterized by X-ray diffraction, Infrared Attenuated Total Reflectance and Raman spectroscopies, elemental analysis, 'Boehm' titration, measurements of pHPZC, nitrogen adsorption isotherms, scanning electron microscopy and differential scanning calorimetry. Sawdust and activated carbon were investigated as bio-adsorbents for boron removal from freshwater. Sawdust showed the highest boron adsorption uptake (1.58 mg g −1 ) compared to activated carbon (0.97 mg g −1 ). This higher capacity was caused by the presence of hydroxylic, carboxylic, and polyphenolic groups. FTIR analysis before and after adsorption of boron suggested that the mechanism involved in the boron removal might be complexation. Langmuir model has the best fitness quality with experimental data, as it gave the maximum R 2 value (0.99).